2022
DOI: 10.1186/s12951-022-01308-w
|View full text |Cite
|
Sign up to set email alerts
|

Continuous ZnO nanoparticle exposure induces melanoma-like skin lesions in epidermal barrier dysfunction model mice through anti-apoptotic effects mediated by the oxidative stress–activated NF-κB pathway

Abstract: Background Increasing interest in the hazardous properties of zinc oxide nanoparticles (ZnO NPs), commonly used as ultraviolet filters in sunscreen, has driven efforts to study the percutaneous application of ZnO NPs to diseased skin; however, in-depth studies of toxic effects on melanocytes under conditions of epidermal barrier dysfunction remain lacking. Methods Epidermal barrier dysfunction model mice were continuously exposed to a ZnO NP-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Numerous studies have shown that ZnO NPs-induced toxicity is associated with NF-κB, Nrf2, and HIF-1α/BNIP3/LC3B-mediated mitochondrial autophagy pathways [ 55 57 ], and this study focuses more on NF-κB pathway based on transcriptome analysis. NF-κB is a sequence-specific DNA-binding transcription factor that is over-activated in almost all cancers [ 58 ] and plays a central role in the initiation and progression of oxidative stress [ 44 , 59 , 60 ], there are multiple evidence shows that the NF-κB signaling pathway is closely connected with cell apoptosis and ferroptosis [ 20 , 61 , 62 ]. As a NF-κB/p65-regulated factor, ZnO NP is involved in the inflammatory responses thereby delaying the recovery of skin diseases and leading to acute lung injury [ 56 , 58 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that ZnO NPs-induced toxicity is associated with NF-κB, Nrf2, and HIF-1α/BNIP3/LC3B-mediated mitochondrial autophagy pathways [ 55 57 ], and this study focuses more on NF-κB pathway based on transcriptome analysis. NF-κB is a sequence-specific DNA-binding transcription factor that is over-activated in almost all cancers [ 58 ] and plays a central role in the initiation and progression of oxidative stress [ 44 , 59 , 60 ], there are multiple evidence shows that the NF-κB signaling pathway is closely connected with cell apoptosis and ferroptosis [ 20 , 61 , 62 ]. As a NF-κB/p65-regulated factor, ZnO NP is involved in the inflammatory responses thereby delaying the recovery of skin diseases and leading to acute lung injury [ 56 , 58 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is a sequence-specific DNA-binding transcription factor that is over-activated in almost all cancers [ 58 ] and plays a central role in the initiation and progression of oxidative stress [ 44 , 59 , 60 ], there are multiple evidence shows that the NF-κB signaling pathway is closely connected with cell apoptosis and ferroptosis [ 20 , 61 , 62 ]. As a NF-κB/p65-regulated factor, ZnO NP is involved in the inflammatory responses thereby delaying the recovery of skin diseases and leading to acute lung injury [ 56 , 58 , 63 ]. MicroRNA is a kind of key non-coding RNA (ncRNAs), 18–22 nt, which mainly binds to gene’s 3′UTR and regulates their expression In KGN cells, the NF-κB signaling pathway was negatively regulated by miR-93-5p to promote apoptosis and ferroptosis [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that ZnO-NP treatment may lead to prostate cancer cell apoptosis and death (26). ZnO-NPs stimulate oxidative stress to induce melanoma-like skin lesions and apoptosis of melanoma cells in mice with epidermal barrier dysfunction through the activation of the NF-κB pathway (27,28). A recent study indicated that ZnO-NPs can promote OC cell death, thus inhibiting the progression of OC (29).…”
Section: Discussionmentioning
confidence: 99%
“…The obtained results showed that, in a mouse model of epidermal barrier dysfunction, topical exposure to ZnO NPs causes these particles to penetrate the stratum basale of the epidermis, leading to the development of melanoma-like lesions on the skin. Additionally, both in vivo and in vitro, persistent exposure to ZnO NPs caused an anti-apoptotic effect in melanocytes through activating NF-κB pathways through oxidative stress [128].…”
Section: Treatment Of a Variety Of Skin Disordersmentioning
confidence: 99%